Bombax ceiba is a Good Native Tree Species for Performing Reforestation to Restore Highly Degraded Tropical Forests in Hainan Island, China - Luo, Jinhuan; Hong, Wenjun; Yang, Jindian; Jiang, Kai; Tan, Zhaoyuan; He, Qifang; Zhang, Hui; Cui, Jie (Frontiers in Environmental Science, 2021)
Reforestation is an effective way to alleviate deforestation and its negative impacts on ecosystem services. It is widely recognized that the most key step for reforestation is using suitable native species, but selecting suitable native tree species is much more complex and challenging than the selection of non-native tree species that have been widely used for reforestation. Here we quantify whether the native tree species (Bombax ceiba) can be suitable for performing reforestation to restore a 0.2 km2 highly degraded tropical monsoon forest in Baopoling Mountain (BPL), Sanya, China, due to 20 years’ limestone mining for cement production. We found that stomatal closure helped Bombax ceiba develop higher drought stress tolerance than the most dominant native tree species (Bridelia tomentosa) in undisturbed tropical rainforest in BPL, thereby to better adapt well to the drought stress in the dry season. These characteristics in turn facilitated it to have high survival rate (92%±4%) and fast-growing, after three years’ monoculture in BPL. Thus, Bombax ceiba is very fit for performing reforestation to recover highly degraded tropical forests in Hainan island, China.